Safety behaviour in the construction sector. Report to the health and safety authority, Dublin & the health and safety executive, Northern Ireland - McDonald, Nick; Hrymak, Victor (Dublin, 2002)
"A multifaceted study of occupational safety culture and habits in the Irish construction industry."